Răspunsuri

2014-09-25T16:38:55+03:00
A) 3*x+7(a+b) => 3*5+7*13 = 15+ 91=106
b) x(a+b)-50= 5*13-50=15
c) 10*x-4(a+b) =5*10-4*13= -2
d) [4(a+b)-2x]*[2(a+b)+x] = (4*13-2*5)*(2*13+5)=42*31=1302
Cel mai inteligent răspuns!
2014-09-25T17:06:57+03:00
A) 3 * 5 + 7(a + b) = 15 + 7 * 13 = 15 + 91 = 106
b) x(a + b) - 50 = 5 * 13 - 50 = 65 - 50 = 15
c) 10 * 5 - 4(a + b) = 50 - 4 * 13 = 50 - 52 = -2
d) {4(a + b) - 2 * 5} * {2(a + b) + 5} = (4 * 13 - 10) * (2 * 13 + 5) = (52 - 10) * ( 26 + 5) = 
42 * 31 = 1302
4 4 4